Method for resisting oxygen corrosion of N80 oil well pipe steel and application thereof

By using laser cladding technology on N80 oil well pipe steel, the problem of oxygen corrosion prone to oil well pipes is solved, and the effect of significantly improving oxygen corrosion resistance and binding force is achieved.

CN119433529APending Publication Date: 2025-02-14CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310945029.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the salt hole compressed air energy storage system, the oil well pipe is prone to oxygen corrosion under humid air and alternating stress conditions, threatening the safe and stable operation of the system.

Method used

Laser cladding technology is used to form a FeCrNiAl mixed powder coating with a thickness of 1.5-3.0 mm on the N80 oil well tube steel substrate, and the Fe, Cr, Ni, and Al content in the coating increases from the contact surface to the surface gradient.

Benefits of technology

It significantly improves the oxygen corrosion resistance of the oil well pipe, enhances the bonding force between the coating and the pipe, reduces the preparation cost, and extends the service life of the pipe column.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433529A_ABST
    Figure CN119433529A_ABST
Patent Text Reader

Abstract

The invention provides a method for resisting oxygen corrosion of N80 oil well pipe steel and application of the method, and the method comprises the following steps: powder is subjected to laser cladding, and a coating with the thickness of 1.5-3.0 mm is formed on an N80 oil well pipe steel matrix; wherein the powder comprises N80 oil well pipe steel powder and FeCrNiAl mixed powder, and the FeCrNiAl mixed powder is composed of element powder with the molar ratio of Fe to Cr to Ni to Al being 50: 20: 25: 5; the contents of Fe, Cr, Ni and Al in the coating are gradually increased in a gradient manner from the contact surface of the coating and the N80 oil well pipe steel substrate to the surface of the coating, and the mass fraction of the FeCrNiAl mixed powder is changed from 25% to 100% in a gradient manner when the weight of the powder is 100%. According to the oxygen corrosion resisting method, the oxidation corrosion resisting performance can be greatly improved, the coating binding force is high, and the pipe preparation cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of corrosion-resistant oil well pipes, and particularly relates to a method for resisting oxygen corrosion of N80 oil well pipe steel and application thereof. Background Art

[0002] During the operation of the salt cavern compressed air energy storage system, when electricity consumption is low, air needs to be injected into the energy storage reservoir through the pipe string; when electricity consumption is peak, air needs to be released from the energy storage reservoir to generate electricity. Therefore, the injection and production pipe string of the energy storage reservoir is the only channel for compressed air to flow through the compressed air energy storage reservoir, and it has two functions: gas injection and gas production. When the pipe string is in service, it is exposed to harsh conditions of humid air and alternating stress for a long time, and is prone to corrosion failure such as oxygen corrosion, which threatens the safe and stable operation of the salt cavern compressed air energy storage system. Therefore, it is urgent to develop oil well pipes for compressed air energy storage reservoirs that are resistant to oxygen corrosion. Summary of the invention

[0003] In order to solve the above problems, the purpose of the present invention is to provide a method for N80 oil well pipe steel to resist oxygen corrosion and its application. The method for resisting oxygen corrosion can not only greatly improve the oxidation corrosion resistance, but also has strong coating bonding and low pipe preparation cost.

[0004] In order to achieve the above object, the present invention provides a method for improving oxygen corrosion resistance of N80 oil well pipe steel, which comprises the following steps: subjecting powder to laser cladding to form a coating with a thickness of 1.5-3.0 mm on a N80 oil well pipe steel substrate; wherein the powder comprises N80 oil well pipe steel powder and FeCrNiAl mixed powder, and the FeCrNiAl mixed powder is composed of element powders with a molar ratio of Fe:Cr:Ni:Al=(48-53):(17-22):(23-27):(3-7) (preferably 50:20:25:5); from the contact surface between the coating and the N80 oil well pipe steel substrate to the surface of the coating, the contents of Fe, Cr, Ni and Al in the coating increase gradually, and the mass fraction of the FeCrNiAl mixed powder changes gradually from 25% to 100% based on the weight of the powder as 100%.

[0005] According to a specific embodiment of the present invention, preferably, the coating is a superposition of 2-3 sub-coatings formed 2-3 times.

[0006] According to a specific embodiment of the present invention, preferably, the coating is a superposition of three sub-coatings formed three times, and from the contact surface between the coating and the N80 oil well pipe steel substrate to the surface of the coating, the coating includes three sub-coatings: a first sub-coating, a second sub-coating, and a third sub-coating.

[0007] According to a specific embodiment of the present invention, preferably, based on the weight of the first sub-powder forming the first sub-coating as 100%, the content of FeCrNiAl mixed powder in the first sub-powder is 25-35wt%; based on the weight of the second sub-powder forming the second sub-coating as 100%, the content of FeCrNiAl mixed powder in the second sub-powder is 65-75wt%; based on the weight of the third sub-powder forming the third sub-coating as 100%, the content of FeCrNiAl mixed powder in the third sub-powder is ≥98wt%.

[0008] According to a specific embodiment of the present invention, preferably, the thickness of the first sub-coating layer is 0.6-1.0 mm.

[0009] According to a specific embodiment of the present invention, preferably, the thickness of the second sub-coating layer is 0.6-1.0 mm.

[0010] According to a specific embodiment of the present invention, preferably, the thickness of the third sub-coating layer is 1.0-1.5 mm.

[0011] According to a specific embodiment of the present invention, preferably, the thickness of the first sub-coating: the thickness of the second sub-coating: the thickness of the third sub-coating = 0.5-1.0: 0.5-1.0: 0.5-1.5, more preferably 0.6-1.0: 0.6-1.0: 1.0-1.5.

[0012] The present invention can reduce residual stress to the greatest extent and improve surface strength by optimizing the thickness of each sub-coating and the thickness ratio and composition of each sub-coating.

[0013] According to a specific embodiment of the present invention, the powder required for each sub-coating is configured, comprising the following specific steps:

[0014] (1) preparing powders according to a mass ratio of FeCrNiAl mixed powder (Fe powder, Cr powder, Ni powder, Al powder molar ratio = 50:20:25:5) / N80 oil well pipe steel powder = 25-35:75-65, adding the prepared powders into a ball mill, and ball milling and mixing to obtain powders required for the first sub-coating;

[0015] (2) preparing powders according to a mass ratio of FeCrNiAl mixed powder (Fe powder, Cr powder, Ni powder, Al powder molar ratio = 50:20:25:5) / N80 oil well pipe steel powder = 65-75:35-25, adding the prepared powders into a ball mill, and ball milling and mixing to obtain powders required for the second sub-coating;

[0016] (3) Powders were prepared according to the mass ratio of FeCrNiAl mixed powder (Fe powder, Cr powder, Ni powder, Al powder molar ratio = 50:20:25:5) / N80 oil well pipe steel powder = 98-100:2-0, and the prepared powders were added into a ball mill, and the powders required for the third sub-coating were obtained by ball milling and mixing.

[0017] According to a specific embodiment of the present invention, the above-mentioned method for resisting oxygen corrosion of N80 oil well pipe steel comprises the following specific steps:

[0018] (1) preparing powder materials required for the first sub-coating, powder materials required for the second sub-coating, and powder materials required for the third sub-coating;

[0019] (2) Layer-by-layer laying + laser cladding:

[0020] The powder required for the first sub-coating is laid on the N80 oil well pipe steel substrate, and the first sub-coating is obtained by laser cladding;

[0021] Laying powder material required for the second sub-coating on the first sub-coating, and obtaining the second sub-coating by laser cladding;

[0022] Laying powder required for the third sub-coating on the second sub-coating, and obtaining the third sub-coating by laser cladding;

[0023] (3) Cooling to complete the oxygen corrosion resistance treatment of N80 oil well pipe steel.

[0024] According to a specific embodiment of the present invention, preferably, the purity of the element powder is ≥99.5%.

[0025] According to a specific embodiment of the present invention, preferably, the particle size of the element powder is 100-300 mesh, and the particle size of the N80 oil well pipe steel powder is 1-8 μm.

[0026] According to a specific embodiment of the present invention, preferably, the powder is mixed by low-energy ball milling before use, and the specific steps are as follows: the N80 oil well pipe steel powder and the FeCrNiAl mixed powder weighed according to the mass fraction are mixed and added into a ball mill, vacuumed, and low-energy ball milled. After the ball milling, the powder is cooled for 30 minutes before being taken out; the powder after ball milling has uniform element distribution and is suitable as laser cladding powder.

[0027] According to a specific embodiment of the present invention, preferably, the ball-to-material mass ratio of the low-energy ball milling method is 5:1-10:1, the rotation speed is 100-150r / min, and the ball milling time is 1h-2h; the rotation speed is more preferably 100r / min, which can prevent Al powder from agglomerating and growing during the ball milling process.

[0028] According to a specific embodiment of the present invention, preferably, the ball milling tank is a vacuum stainless steel tank, a cemented carbide tank or an agate tank.

[0029] According to a specific embodiment of the present invention, preferably, the balls used in the low-energy ball milling method are one or a combination of two or more of stainless steel balls, cemented carbide balls and zirconia balls.

[0030] According to a specific embodiment of the present invention, preferably, the low energy ball milling method does not use ball milling media.

[0031] According to a specific embodiment of the present invention, preferably, a process control agent is added during the ball milling process, and the process control agent includes one or a combination of two or more of anhydrous ethanol, n-heptane, and stearic acid.

[0032] According to a specific embodiment of the present invention, preferably, the N80 oil well pipe steel substrate is degreased and derusted before laser cladding, and the surface of the N80 oil well pipe steel substrate is clean and dry. Common degreasing and derusting treatments include: grinding or sandblasting the substrate with #400-#800 sandpaper, and then cleaning the surface impurities and oil stains with anhydrous ethanol or acetone.

[0033] According to a specific embodiment of the present invention, preferably, the laser power of the laser cladding is 800-2500W, the spot size is 4mm, and the scanning speed is 3-5mm / s; a laser such as Laserline 4.4KW high-power semiconductor fiber-coupled laser is used.

[0034] The present invention also provides a method for resisting oxygen corrosion of a pipe column for a compressed air energy storage reservoir, which adopts the above-mentioned method for resisting oxygen corrosion of the N80 oil well pipe steel.

[0035] The present invention also provides an N80 oil well pipe steel material having an oxygen corrosion resistant coating, wherein the oxygen corrosion resistant coating comprises N80 and FeCrNiAl, wherein the molar ratio of Fe:Cr:Ni:Al is 50:20:25:5; and, from the contact surface between the coating and the N80 oil well pipe steel substrate to the surface of the coating, the contents of Fe, Cr, Ni and Al in the coating increase gradually, and the mass fraction of FeCrNiAl changes gradually from 25% to 100% when the total weight of N80 and FeCrNiAl is 100%.

[0036] The present invention uses laser cladding to prepare a corrosion-resistant metal coating with a gradient composition layer by layer on the inner wall of carbon steel. This can effectively solve the problems of the oil casing (organic coating and low-alloy steel pipe) used in compressed air energy storage tanks being easy to age and peel off during long-term service, and the steel pipe having a greater risk of oxygen corrosion. It can extend the service life of the downhole pipe column and improve the anti-oxidation corrosion ability of the pipe column and the bonding strength between the coating and the pipe column under the condition of meeting low cost. Compared with the prior art, the present invention has the following characteristics:

[0037] (1) The N80 / FeCrNiAl gradient coating prepared by laser cladding has high surface hardness and good wear resistance. Due to the uniqueness of the laser cladding method, the produced coating has strong bonding strength and is not easy to peel off;

[0038] (2) Compared with the alloy coating under the same conditions, the three layers of coating with different N80 / FeCrNiAl contents, in which the N80 content decreases, are beneficial to improving the bonding ability between the coating and the N80 substrate and are not easy to peel off;

[0039] (3) The coating prepared by this method has low cost, simple operation and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of laser cladding equipment.

[0041] Explanation of symbols:

[0042] 1-laser beam, 2-laser cladding composite powder, 3-water-cooled powder nozzle, 4-molten pool, 5-cladding coating, 6-substrate material to be clad. DETAILED DESCRIPTION

[0043] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0044] Example 1

[0045] This embodiment provides a method for laser cladding of an oxygen corrosion resistant N80 / FeCrNiAl gradient coating, the steps of which are as follows:

[0046] (1) Fe, Cr, Ni, and Al element powders are selected and mixed in an atomic ratio of 50:20:25:5 to obtain FeCrNiAl mixed powder, which is then mixed with N80 oil well pipe steel powder to obtain powders with a mass fraction of 67wt%, 33wt%, and 0wt% of N80 oil well pipe steel powder (the mass fraction is calculated based on the sum of the mass of the FeCrNiAl mixed powder and the N80 oil well pipe steel powder being 100%); the purity of the metal powder is greater than 99.5%, the particle size is 100-300 mesh, and the particle size of the N80 oil well pipe steel powder is 2μm;

[0047] (2) The mixed powder was prepared by low-energy ball milling: the mixed powders were added to the ball mill respectively, vacuumed, the ball-to-material mass ratio was controlled to be 5:1, the rotation speed was 100 r / min, the ball milling time was 2 h, the two powders were mixed evenly, and after the ball milling was completed, the powder was cooled for 30 minutes before taking out; the ball mill used was a vacuum stainless steel tank, the balls used were stainless steel balls, and no ball milling medium was added;

[0048] (3) Pre-treating the N80 oil well pipe steel substrate, including the following steps: cleaning, drying, grinding or sandblasting with #400 and #800 sandpaper, and cleaning the surface impurities and oil stains with anhydrous ethanol or acetone;

[0049] (4) Pre-laying the FeCrNiAl+67wt%N80 powder prepared in step (1) on the surface of the substrate, and then compacting it to form a preset layer with a thickness of 1 mm;

[0050] (5) The pre-deposited layer in step (2) was subjected to laser cladding treatment, with a laser power of 1000 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0051] (6) After the first sub-coating layer obtained in step (5) is polished with #400 sandpaper, the FeCrNiAl+33wt%N80 powder prepared in step (1) is pre-laid on the surface of the first sub-coating layer, and then compacted to form a pre-layer with a thickness of 1 mm;

[0052] (7) The pre-deposited layer in step (6) was subjected to laser cladding treatment, with a laser power of 900 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0053] (8) After the second sub-coating layer obtained in step (7) is polished with #400 sandpaper, the FeCrNiAl+0wt%N80 powder prepared in step (1) is pre-laid on the surface of the sample and then compacted to form a pre-layer with a thickness of 1 mm;

[0054] (9) The pre-deposited layer in step (8) is subjected to laser cladding treatment, with the same parameters as step (7).

[0055] (10) The obtained sample was air-cooled to room temperature.

[0056] Schematic diagram of laser cladding equipment Figure 1 shown.

[0057] Example 2

[0058] This embodiment provides a method for laser cladding of an oxygen corrosion resistant N80 / FeCrNiAl gradient coating, the steps of which are as follows:

[0059] (1) Fe, Cr, Ni, and Al element powders are selected and mixed in an atomic ratio of 50:20:25:5 to obtain FeCrNiAl mixed powder, which is then mixed with N80 oil well pipe steel powder to obtain powders with a mass fraction of 75wt%, 25wt%, and 0wt% of N80 oil well pipe steel powder (the mass fraction is calculated based on the sum of the mass of the FeCrNiAl mixed powder and the N80 oil well pipe steel powder being 100%); the purity of the metal powder is greater than 99.5%, the particle size is 100-300 mesh, and the particle size of the N80 oil well pipe steel powder is 2 μm;

[0060] (2) The mixed powder was prepared by low-energy ball milling: the mixed powders were added to the ball mill respectively, vacuumed, the ball-to-material mass ratio was controlled to be 5:1, the rotation speed was 100 r / min, the ball milling time was 2 h, the two powders were mixed evenly, and after the ball milling was completed, the powder was cooled for 30 minutes before taking out; the ball mill used was a vacuum stainless steel tank, the balls used were stainless steel balls, and no ball milling medium was added;

[0061] (3) Pre-treating the N80 oil well pipe steel substrate, including the following steps: cleaning, drying, grinding or sandblasting with #400 and #800 sandpaper, and cleaning the surface impurities and oil stains with anhydrous ethanol or acetone;

[0062] (4) Pre-laying the FeCrNiAl+75wt%N80 powder prepared in step (1) on the surface of the substrate, and then compacting it to form a pre-layer with a thickness of 1 mm;

[0063] (5) The pre-deposited layer in step (2) was subjected to laser cladding treatment, with a laser power of 1000 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0064] (6) After the first sub-coating layer obtained in step (5) is polished with #400 sandpaper, the FeCrNiAl+25wt%N80 powder prepared in step (1) is pre-laid on the surface of the first sub-coating layer, and then compacted to form a pre-layer with a thickness of 1 mm;

[0065] (7) The pre-deposited layer in step (6) was subjected to laser cladding treatment, with a laser power of 900 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0066] (8) After the second sub-coating layer obtained in step (7) is polished with #400 sandpaper, the FeCrNiAl+0wt%N80 powder prepared in step (1) is pre-laid on the surface of the sample and then compacted to form a pre-layer with a thickness of 1 mm;

[0067] (9) The pre-deposited layer in step (8) is subjected to laser cladding treatment, with the same parameters as step (7).

[0068] (10) The obtained sample was air-cooled to room temperature.

[0069] Comparative Example 1

[0070] This comparative example provides a method for laser cladding of an oxygen corrosion resistant N80 / FeCrNiAl gradient coating, the steps of which are as follows:

[0071] (1) Fe, Cr, Ni, and Al element powders are selected and mixed in an atomic ratio of 50:20:25:5 to obtain FeCrNiAl mixed powder, which is then mixed with N80 oil well pipe steel powder to obtain powders with a mass fraction of 67wt% and 0wt% of N80 oil well pipe steel powder (the mass fraction is calculated based on the sum of the mass of the FeCrNiAl mixed powder and the N80 oil well pipe steel powder being 100%); the purity of the metal powder is greater than 99.5%, the particle size is 100-300 mesh, and the particle size of the N80 oil well pipe steel powder is 2μm;

[0072] (2) The mixed powder was prepared by low-energy ball milling: the mixed powders were added to the ball mill respectively, vacuumed, the ball-to-material mass ratio was controlled to be 5:1, the rotation speed was 100 r / min, the ball milling time was 2 h, the two powders were mixed evenly, and after the ball milling was completed, the powder was cooled for 30 minutes before taking out; the ball mill used was a vacuum stainless steel tank, the balls used were stainless steel balls, and no ball milling medium was added;

[0073] (3) Pre-treating the N80 oil well pipe steel matrix, including the following steps: cleaning, drying, grinding or sandblasting with #400 and #800 sandpaper, and cleaning the impurities and oil stains on the surface with anhydrous ethanol or acetone;

[0074] (4) Pre-laying the FeCrNiAl+67wt%N80 powder prepared in step (1) on the surface of the substrate, and then compacting it to form a preset layer with a thickness of 1 mm;

[0075] (5) The pre-deposited layer in step (2) was subjected to laser cladding treatment, with a laser power of 1000 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0076] (6) After the first sub-coating layer obtained in step (5) is polished with #400 sandpaper, the FeCrNiAl+0wt%N80 powder prepared in step (1) is pre-laid on the surface of the first sub-coating layer, and then compacted to form a pre-layer with a thickness of 1 mm;

[0077] (7) The pre-deposited layer in step (6) was subjected to laser cladding treatment, with a laser power of 900 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0078] (8) After the second sub-coating layer obtained in step (7) is polished with #400 sandpaper, the FeCrNiAl+0wt%N80 powder prepared in step (1) is pre-laid on the surface of the sample and then compacted to form a pre-layer with a thickness of 1 mm;

[0079] (9) The pre-deposited layer in step (8) is subjected to laser cladding treatment, with the same parameters as step (7).

[0080] (10) The obtained sample was air-cooled to room temperature.

[0081] Comparative Example 2

[0082] This comparative example provides a method for laser cladding of an oxygen corrosion resistant N80 / FeCrNiAl gradient coating, the steps of which are as follows:

[0083] (1) Fe, Cr, Ni, and Al element powders are selected and mixed in an atomic ratio of 50:20:25:5 to obtain FeCrNiAl mixed powder, which is then mixed with N80 oil well pipe steel powder to obtain a powder with a mass fraction of 67wt% of N80 oil well pipe steel powder (the mass fraction is calculated based on the sum of the masses of the FeCrNiAl mixed powder and the N80 oil well pipe steel powder being 100%); the purity of the metal powder is greater than 99.5%, the particle size is 100-300 mesh, and the particle size of the N80 oil well pipe steel powder is 2μm;

[0084] (2) The mixed powder was prepared by low-energy ball milling: the mixed powders were added to the ball mill respectively, vacuumed, the ball-to-material mass ratio was controlled to be 5:1, the rotation speed was 100 r / min, the ball milling time was 2 h, the two powders were mixed evenly, and after the ball milling was completed, the powder was cooled for 30 minutes before taking out; the ball mill used was a vacuum stainless steel tank, the balls used were stainless steel balls, and no ball milling medium was added;

[0085] (3) Pre-treating the N80 oil well pipe steel matrix, including the following steps: cleaning, drying, grinding or sandblasting with #400 and #800 sandpaper, and cleaning the impurities and oil stains on the surface with anhydrous ethanol or acetone;

[0086] (4) Pre-laying the FeCrNiAl+67wt%N80 powder prepared in step (1) on the surface of the substrate, and then compacting it to form a preset layer with a thickness of 1 mm;

[0087] (5) The pre-deposited layer in step (2) was subjected to laser cladding treatment, with a laser power of 1000 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0088] (6) After the first sub-coating layer obtained in step (5) is polished with #400 sandpaper, the FeCrNiAl+67wt%N80 powder prepared in step (1) is pre-laid on the surface of the first sub-coating layer, and then compacted to form a pre-layer with a thickness of 1 mm;

[0089] (7) The pre-deposited layer in step (6) was subjected to laser cladding treatment, with a laser power of 900 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0090] (8) After the second sub-coating layer obtained in step (7) is polished with #400 sandpaper, the FeCrNiAl+67wt%N80 powder prepared in step (1) is pre-laid on the surface of the sample and then compacted to form a pre-layer with a thickness of 1 mm;

[0091] (9) The pre-deposited layer in step (8) is subjected to laser cladding treatment, with the same parameters as step (7).

[0092] (10) The obtained sample was air-cooled to room temperature.

[0093] Comparative Example 3

[0094] This comparative example provides a method for laser cladding of an oxygen corrosion resistant N80 / FeCrNiAl gradient coating, the steps of which are as follows:

[0095] (1) Fe, Cr, Ni, and Al element powders are selected and mixed in an atomic ratio of 50:20:25:5 to obtain FeCrNiAl mixed powder, which is then mixed with N80 oil well pipe steel powder to obtain a powder with a mass fraction of 0 wt% of N80 oil well pipe steel powder (the mass fraction is calculated based on the sum of the masses of the FeCrNiAl mixed powder and the N80 oil well pipe steel powder being 100%); the purity of the metal powder is greater than 99.5%, the particle size is 100-300 mesh, and the particle size of the N80 oil well pipe steel powder is 2 μm;

[0096] (2) The mixed powder was prepared by low-energy ball milling: the mixed powders were added to the ball mill respectively, vacuumed, the ball-to-material mass ratio was controlled to be 5:1, the rotation speed was 100 r / min, the ball milling time was 2 h, the two powders were mixed evenly, and after the ball milling was completed, the powder was cooled for 30 minutes before taking out; the ball mill used was a vacuum stainless steel tank, the balls used were stainless steel balls, and no ball milling medium was added;

[0097] (3) Pre-treating the N80 oil well pipe steel matrix, including the following steps: cleaning, drying, grinding or sandblasting with #400 and #800 sandpaper, and cleaning the impurities and oil stains on the surface with anhydrous ethanol or acetone;

[0098] (4) Pre-laying the FeCrNiAl+0wt% N80 powder prepared in step (1) on the surface of the substrate, and then compacting it to form a preset layer with a thickness of 1 mm;

[0099] (5) The pre-deposited layer in step (2) was subjected to laser cladding treatment, with a laser power of 1000 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0100] (6) After the first sub-coating layer obtained in step (5) is polished with #400 sandpaper, the FeCrNiAl+0wt%N80 powder prepared in step (1) is pre-laid on the surface of the first sub-coating layer, and then compacted to form a pre-layer with a thickness of 1 mm;

[0101] (7) The pre-deposited layer in step (6) was subjected to laser cladding treatment, with a laser power of 900 W, a spot diameter of 4 mm, a scanning speed of 4 mm / s, and Ar gas protection during the cladding process;

[0102] (8) After the second sub-coating layer obtained in step (7) is polished with #400 sandpaper, the FeCrNiAl+0wt%N80 powder prepared in step (1) is pre-laid on the surface of the sample and then compacted to form a pre-layer with a thickness of 1 mm;

[0103] (9) The pre-deposited layer in step (8) is subjected to laser cladding treatment, with the same parameters as step (7).

[0104] (10) The obtained sample was air-cooled to room temperature.

[0105] Performance Testing

[0106] The coatings prepared in each embodiment and comparative example were subjected to performance tests. Among them, the hardness test was measured using a Vickers hardness tester. The oxidation weight gain experiment was carried out in accordance with GB / T 13303-1991 "Method for Determination of Antioxidant Properties of Steel". The coating adhesion was tested using a scratch method: a conical diamond indenter with a smooth tip was used to scratch the coating surface while gradually increasing the vertical pressure of the indenter. The minimum pressure at which the coating cracked was used to represent the film-substrate adhesion strength. The test results are shown in Table 1.

[0107] Table 1 Performance test results

[0108]

[0109] In Table 1, each example has high hardness and film-substrate bonding strength, low oxidation weight gain, and exhibits excellent comprehensive performance. Compared with the comparative example, it has obvious advantages in coating hardness, bonding strength and oxidation resistance.

[0110] In Comparative Example 1, the coating has only one composition gradient and poor bonding strength; in Comparative Example 2, the coating has only one composition (67% N80 steel), poor oxidation resistance and low hardness; in Comparative Example 3, the coating has only FeCrNiAl and poor bonding strength with the substrate.

Claims

1. A method for resisting oxygen corrosion of N80 oil well pipe steel, comprising the following steps: The powder is laser clad to form a coating with a thickness of 1.5-3.0 mm on the N80 oil well pipe steel substrate; The powder material comprises N80 oil well pipe steel powder and FeCrNiAl mixed powder, wherein the FeCrNiAl mixed powder is composed of element powders with a molar ratio of Fe:Cr:Ni:Al=(48-53):(17-22):(23-27):(3-7); From the contact surface between the coating and the N80 oil well pipe steel substrate to the surface of the coating, the contents of Fe, Cr, Ni and Al in the coating increase gradually. Taking the weight of the powder as 100%, the mass fraction of the FeCrNiAl mixed powder changes gradually from 25% to 100%.

2. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 1, wherein: The coating is a superposition of 2-3 sub-coatings formed 2-3 times.

3. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 2, wherein: The coating is a superposition of three sub-coatings formed three times. From the contact surface between the coating and the N80 oil well pipe steel substrate to the surface of the coating, the coating includes three sub-coatings: a first sub-coating, a second sub-coating, and a third sub-coating.

4. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 3, wherein: Taking the weight of the first sub-powder forming the first sub-coating layer as 100%, the content of the FeCrNiAl mixed powder in the first sub-powder is 25-35wt%; Taking the weight of the second sub-powder forming the second sub-coating layer as 100%, the content of the FeCrNiAl mixed powder in the second sub-powder is 65-75wt%; Taking the weight of the third sub-powder forming the third sub-coating as 100%, the content of the FeCrNiAl mixed powder in the third sub-powder is ≥98wt%.

5. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 3, wherein: The thickness of the first sub-coating layer is 0.6-1.0 mm; Preferably, the thickness of the second sub-coating layer is 0.6-1.0 mm; Preferably, the third sub-coating layer has a thickness of 1.0-1.5 mm.

6. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 3, wherein: The thickness of the first sub-coating: the thickness of the second sub-coating: the thickness of the third sub-coating=0.5-1.0:0.5-1.0:0.5-1.5, preferably 0.6-1.0:0.6-1.0:1.0-1.

5.

7. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 2 or 3, wherein: The method for resisting oxygen corrosion of N80 oil well pipe steel comprises the following steps: (1) preparing powder materials required for the first sub-coating layer, powder materials required for the second sub-coating layer, and powder materials required for the third sub-coating layer; (2) laying the powder required for the first sub-coating on the N80 oil well pipe steel substrate, and laser cladding to obtain the first sub-coating; Laying powder material required for the second sub-coating on the first sub-coating, and obtaining the second sub-coating by laser cladding; Laying powder required for the third sub-coating on the second sub-coating, and obtaining the third sub-coating by laser cladding; (3) Cooling.

8. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 1, wherein: The purity of the element powder is ≥99.5%; Preferably, the particle size of the element powder is 100-300 mesh, and the particle size of the N80 oil well pipe steel powder is 1-8 μm.

9. The method for oxygen corrosion resistance of N80 oil well pipe steel according to any one of claims 1 to 8, wherein: The powder is mixed by low-energy ball milling before use; Preferably, the ball-to-material mass ratio of the low-energy ball milling method is 5:1-10:1, the rotation speed is 100-150 r / min, and the ball milling time is 1h-2h; the rotation speed is preferably 100 r / min; Preferably, the ball milling tank is a vacuum stainless steel tank, a hard alloy tank or an agate tank; Preferably, the balls used in the low-energy ball milling method are one or a combination of two or more of stainless steel balls, cemented carbide balls, and zirconia balls; Preferably, the low energy ball milling method does not use ball milling media; Preferably, a process control agent is added during the ball milling process, and the process control agent includes one or a combination of two or more of anhydrous ethanol, n-heptane, and stearic acid.

10. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 1, wherein: The N80 oil well pipe steel substrate is degreased and derusted before laser cladding.

11. The method for oxygen corrosion resistance of N80 oil well pipe steel according to claim 1, wherein: The laser power of the laser cladding is 800-2500W, the spot size is 4mm, and the scanning speed is 3-5mm / s.

12. A method for resisting oxygen corrosion of a pipe string for a compressed air energy storage reservoir, which adopts the method for resisting oxygen corrosion of N80 oil well pipe steel according to any one of claims 1 to 11.

13. An N80 oil well pipe steel having an oxygen corrosion resistant coating, wherein the oxygen corrosion resistant coating comprises N80 and FeCrNiAl, wherein: The molar ratio of Fe:Cr:Ni:Al is 50:20:25:5; Furthermore, from the contact surface between the coating and the N80 oil well pipe steel substrate to the surface of the coating, the contents of Fe, Cr, Ni and Al in the coating increase gradually, and the mass fraction of FeCrNiAl changes gradually from 25% to 100% when the total weight of N80 and FeCrNiAl is 100%.